62.0k views
4 votes
F(x) = 8x2 – 2x + 3

g(x) = 12x2 + 4x – 3

What is h(x) = f(x) – g(x)?

Options:
h(x) = 20x2 + 2x
h(x) = –4x2 – 6x
h(x) = –4x2 – 6x + 6
h(x) = –4x2 + 2x

2 Answers

3 votes

Answer:
\text{h(x)}=-4x^2-6x+6

Explanation:

Given functions :
\text{f(x) }= 8x^2 - 2x + 3 (1)


\text{g(x)} = 12x^2 + 4x - 3 (2)

To find :
\text{ h(x) = f(x) - g(x)}

Consider :
\text{ h(x) = f(x) - g(x)}

i.e. Subtract the expression for g(x) in equation (2) from the expression for f(x) in (1), we get


\text{ h(x)}=8x^2 - 2x + 3-(12x^2 + 4x -3)

Multiply (-) sign inside the parentheses, we get


\text{ h(x) }=8x^2 - 2x + 3-12x^2 -4x +3

Combine like terms, we get


\text{ h(x) }=8x^2-12x^2 - 2x -4x + 3 +3\\\\\Rightarrow\text{h(x)}=-4x^2-6x+6

Hence, the correct answer is
\text{h(x)}=-4x^2-6x+6

User FatDogMark
by
5.7k points
7 votes

Answer:

Correct option is (C).

Explanation:


f(x) = 8 {x}^(2) - 2x + 3


g(x) = 12 {x}^(2) + 4x - 3

Now,

h (x) =f (x) - g (x)


h(x) = \: 8 {x}^(2) - 2x + 3 - 12 {x}^(2) - 4x + 3


h(x) = - 4 {x}^(2) - 6x + 6

So, correct option is (C).

#$# HOPE YOU UNDERSTAND #$#

#$¥ THANK YOU ¥$#

❤ ☺ ☺ ☺ ☺ ☺ ☺ ❤

User Ten Bitcomb
by
6.0k points